Re-engineering agriculture for enhanced performance through financing - Mafimisebi, Taiwo (2010)
Insufficient institutional credit is a major contributor to the persistent poor performance of the Nigerian agricultural sector. To encourage financial institutions to increase lending to the sector, a partial credit guarantee scheme was instituted. The scheme commenced operations in 1978 with an authorized capital of N 100.00 million, subscribed to 60% and 40% by the Federal Government of Nigeria and the Central Bank of Nigeria, respectively. This paper presents an appraisal of the scheme. The results revealed that there has been continuous growth in paid-up share capital, total fund resources, maximum amount of loan obtainable by farmers, number and value of loans guaranteed, volume and value of loans fully repaid and volume and value of default claims settled. There was a long-run convergence between the number and volume of guaranteed loans and the agricultural GDP. This finding indicates the need to expand the quantum of funds available for guaranteeing agricultural loans to increase performance of the agricultural sector in the long run. This step is justified by the strategic role of agriculture in the Nigerian economy in terms of food and fiber production, job creation, income generation, poverty reduction and economic stability.